Novel Resonant Structure to Compact Partial H-Plane Band-Pass Waveguide Filter - Elahe Mohhamadi; Habib Ghorbaninejad (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper partial H-plane band-pass waveguide filter, utilizing a novel resonant structure comprising a metal window along with metal posts has been proposed to compact the filter size. The metal windows and posts have been implemented transversely in a partial H-plane waveguides, which have one-quarter cross section size compared to the conventional waveguides in the same frequency range. Partial H-plane band-pass waveguide filter with novel proposed resonant structures has considerably shorter longitudinal length compared to the conventional partial H-plane filters, so that they reduce both cross section size and the total length of the filter compared to conventional H-plane filters, in the same frequency range. In the presented design procedure, the size and shape of each metal window and metal posts has been determined by fitting the transfer function of the proposed resonant structure to that of a desired one, which is obtained from a suitable equivalent circuit model. The design process is based on optimization using electromagnetic simulator software, HFSS. A proposed partial H-plane band-pass filter has been designed and simulated to verify usefulness and performance of the design method.